Implementasi Nilai Toleransi untuk Meningkatkan Sikap Anti Bulliying di Madin Baitul Ilmi Desa Tegalombo - Yulfatunaimah, Evi; Prahastiwi, Eka Danik (YASIN, 2025)
Bullying is a serious problem in formal and non-formal educational settings, often normalized despite its negative impacts on victims, such as mental, physical, and psychological distress. This study aims to reduce bullying behavior at Madin Baitul Ilmi Tegalombo by implementing tolerance values to foster mutual respect, dignity, and solidarity. The research employs a qualitative approach with four stages: initial observation, intervention, monitoring, and evaluation. Initial observations revealed that 95% of students engaged in verbal, physical, and social bullying, triggered by factors such as social media influence, family background, and environmental exposure. Interventions were implemented through three strategies: (1) teacher role modeling (uswah hasanah), (2) creating an inclusive classroom environment, and (3) providing positive reinforcement. Post-intervention evaluation showed a significant decline in bullying behavior to 30%, with detailed reductions: mocking (10%), belittling (7%), name-calling (3%), pushing (5%), and hitting (5%). The study concludes that integrating tolerance values rooted in Islamic principles effectively reduces bullying while shaping students’ empathetic, inclusive character and constructive conflict-resolution skills. Practical implications recommend adopting similar approaches in other educational institutions, supported by collaboration among schools, families, and communities to mitigate external factors that trigger bullying.